1993
DOI: 10.1128/mcb.13.10.6393
|View full text |Cite
|
Sign up to set email alerts
|

Human ERCC5 cDNA-cosmid complementation for excision repair and bipartite amino acid domains conserved with RAD proteins of Saccharomyces cerevisiae and Schizosaccharomyces pombe.

Abstract: Several human genes related to DNA excision repair (ER) have been isolated via ER cross-species complementation (ERCC) of UV-sensitive CHO cells. We have now isolated and characterized cDNAs for the human ERCC5 gene that complement CHO UV135 cells. The ERCC5 mRNA size is about 4.6 kb. Our available cDNA clones are partial length, and no single clone was active for UV135 complementation. When cDNAs were mixed pairwise with a cosmid clone containing an overlapping 5'-end segment of the ERCC5 gene, DNA transfer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 65 publications
(89 reference statements)
0
40
0
Order By: Relevance
“…XPG plasmid concentrations were determined by measurement of absorbance at 260 nm and verified by agarose gel electrophoresis and ethidium bromide staining. The XPG-deficient CHO cell line UV135 (16,23) was transfected with a mixture of 150 ng of luciferase plasmid, 150 ng of ␤-galactosidase plasmid (22), and 30 ng of wild-type or mutant XPG plasmid by calcium phosphate precipitation (16). For each XPG transfection set, three to six 60-mm dishes were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…XPG plasmid concentrations were determined by measurement of absorbance at 260 nm and verified by agarose gel electrophoresis and ethidium bromide staining. The XPG-deficient CHO cell line UV135 (16,23) was transfected with a mixture of 150 ng of luciferase plasmid, 150 ng of ␤-galactosidase plasmid (22), and 30 ng of wild-type or mutant XPG plasmid by calcium phosphate precipitation (16). For each XPG transfection set, three to six 60-mm dishes were used.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid 981-1009 fragment of human XPG was amplified by polymerase chain reaction with forward primer 5Ј-CCAGAATTCTTA-AAGCAACTCGATG-3Ј and reverse primer 5Ј-GTGCTCGAGTTA-ACGTTTAGCATCTTCTTTCTC-3 using plasmid pBSK-XPGA (16,17) as template. The EcoRI/XhoI-digested product was ligated with EcoRI/ XhoI-linearized pGEX-4T-1 to create plasmid GST-XPG that expresses a fusion protein of GST and XPG .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing human DNA into a Chinese hamster ovary (CHO) mutant (UV135) (14), the human gene (ERCC5) that corrected UV sensitivity of UV135 was cloned (15,16). Recent genetic and biochemical complementation studies have assigned the ERCC5 gene to the human XPG genotype (17)(18)(19).…”
mentioning
confidence: 99%
“…While studying tRNA transcription, the laboratory of Stuart Clarkson isolated cDNAs encoding frog and human homologs of the yeast RAD2 gene (the XPG equivalent in Saccharomyces cerevisiae) and demonstrated that the human cDNA was able to complement the UV sensitivity of XP-G cells. 9 XP-G cells were subsequently found to be equivalent to Chinese hamster ovary (CHO) cells from complementation group ERCC5, [10][11][12] and the XPG gene was mapped at chromosome 13q32-33. 13,14 Biochemical properties of the XPG protein Analysis of the primary sequence of XPG quickly revealed that it harbors two nuclease domains placing it in the Fen1 family of structure-specific endonucleases.…”
Section: Discovery and Cloning Of Xpgmentioning
confidence: 99%